The oxidation of naphthalene and pyrene by cytochrome P450cam. - England, P; Harford-Cross, C; Stevenson, J; Rouch, D; Wong, L (1998)
Mutants of the heme monooxygenase cytochrome P450cam in which Y96 had been replaced with hydrophobic residues, have been shown to oxidise naphthalene and pyrene with rates one to two orders of magnitude faster than the wild-type. Naphthalene was oxidised to 1- and 2-naphthol, probably via the 1,2-oxide intermediate. In the case of the Y96F mutant, naphthalene was oxidised at a rate comparable to camphor. Pyrene oxidation gave 1,6- and 1,8-pyrenequinone with no evidence for attack at the K-region, in contrast to mammalian enzymes. The results show that the Y96 residue plays a key role in controlling the substrate range of P450cam.